Empowering Women through Social Entrepreneurship: A Literature Review - Fadila JEHHAD; HAOUCHA Malika (Communications of International Proceedings, 2022)
Women's empowerment has received significant academic attention throughout the past decade. While an extensive part of women's empowerment literature has studied the role of social entrepreneurship under the form of case studies. This  review follows a systematic approach and analyzes the concepts of social entrepreneurship and women’s empowerment separately and the relationship between the two within multiple fields while enhancing the similarities and differences of the case studies.
Keywords: Women’s empowerment; social entrepreneurship